Tantangan Komunikasi di Era Digital: Memahami Generasi Z - Yulianti Fajar Wulandari; Mareta Puri Rahastine; Heri Afianto; Yan Bastian; Murtiadi Murtiadi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The aim of this research is to analyze Communication Challenges in the Digital Era and Understanding Generation Z. This research is a Literature review. Data collection using documentation from Google School. Data analysis using Systematic Literature Review (SLR). Communication challenges in the current digital era, especially in interacting with Generation Z, is a very wide expansion of the communication field through various digital platforms, such as social media, instant messaging, and online content. Generation Z has unique characteristics that influence the way they communicate, such as a preference for short messages, images and videos that are effective in conveying messages. Understanding and adapting your communication style to them is important for building strong and effective relationships. In addition, it must be acknowledged that Generation Z has a high level of technological awareness, which can raise privacy and security issues that must be managed wisely in an effort to establish successful communication with this generation.